TREATMENT OF GINGIVAL FIBROMATOSIS IN PEDIATRIC PATIENTS - Giacomo Gobbo Trojan; Julia Yanes Moia Vivan; Katiane Vieira Menezes Leite; Alice Jacques de Borba; Larissa Caroline Bruchez Pereira (International Journal of Health Management Review, 2026)
Gingival fibromatosis is a rare condition characterized by the excessive and progressive enlargement of gingival tissue, which may occur in isolation or in association with genetic syndromes. In pediatric patients, this hyperplasia can interfere with tooth eruption, mastication, speech, oral hygiene, and aesthetics. The aim of this review was to synthesize available evidence regarding the diagnosis and treatment of gingival fibromatosis in pediatric patients, emphasizing associated genetic conditions, therapeutic modalities, and recurrence rates. A narrative literature review was conducted using the PubMed database in August 2026, employing the search strategies "Treatment of gingival fibromatosis" AND "Child" and "Gingival fibromatosis" AND "Child." Seven studies published within the last five years, available in full text in Portuguese or English, were selected. The results demonstrated that diagnosis must take into account clinical, histopathological, and genetic findings. Management involves oral hygiene control and interventions such as gingivectomy or gingivoplasty when functional or aesthetic impairment is present. Recurrence remains the primary challenge, underscoring the importance of continuous follow-up.